Association of Socio Demographic Characteristics and Husband Social Supports to the Participation of Mother in Antenatal Class - Ni Ketut Nopi Widiantari; Ni Luh Putu Suariyani; I Nyoman Mangku Karmaya (Universitas Udayana, 2016)
Background and purpose: Antenatal class has been applied in three different health centers located in Denpasar to increase maternal and child health with group learning method about pregnancy, delivery, post natal care, infant care and others. However, attendances of pregnant mothers were low. The aim of this study was to investigate association between mother’s characteristics and husband’s social supports to their participation in attending the antenatal class. Methods: This study was a cross-sectional survey involving 122 samples. Samples were pregnant mothers whom was selected by systematic random sampling from antenatal registration book. Data were collected by interview conducted in their house or when they were visiting the clinics. Data were analyzed by univariate, bivariate (chi square test) and multvariate (poisson regression method). Results: Proportion of mother attended antenatal class in three different health centers was 29.5%. Bivariate analysis showed that variables which associated with mother attendance were parity (p=0.036), husband social support (p=0.001) which include emotional support (p=0.001), instrumental support (p=0.001) and reward. Multivariate analysis showed that the only variable related to mother attendance in the antenatal class was husband social support (PR=2.71; 95%CI: 8.13-90.46). Conclusions: The attendance of mother in antenatal class in three different clinics were low. Factors that influence the attendance of mother was social support from husband.